Elevated expression of PTCD3 correlates with tumor progression and predicts poor prognosis in patients with prostate cancer - Huang, Yiqiao (Mol Med Rep, 2018)
Pentatricopeptide repeat domain protein 3 (PTCD3) is a mitochondrial RNA-binding protein that serves a role in mitochondrial translation. PTCD3 was originally reported as an oncogene that is involved in breast cancer and lymphoma. However, the expression and function of PTCD3 in prostate cancer (PCa) are unknown. Therefore, the aim of the present study was to investigate the expression of PTCD3 and its clinical significance in PCa. Immunohistochemistry and dataset analyses revealed that PTCD3 protein expression levels were enhanced in human PCa tissues and mouse PCa models. PTCD3 expression levels were positively correlated with advanced PCa pathological grade and clinical stage. Additionally, PTCD3 mRNA expression was positively correlated with tissue malignancy, high Gleason score and distant metastasis in The Cancer Genome Atlas dataset. Kaplan-Meier analysis revealed that high PTCD3 levels can predict the increased biochemical recurrence (BCR)-free survival in all patients with or without metastasis. The overexpression of PTCD3 could be used as an independent prognostic marker of poor BCR-free survival. Immunofluorescence and western blot analysis in human PCa cell lines further confirmed that PTCD3 levels were associated with the hormone independence of PCa. Therefore, the present study revealed that PTCD3 levels may serve as a novel biomarker for PCa prognosis.